An assessment of people living by coral reefs over space and time. (28th September 2022) - Sing Wong, Amy; Vrontos, Spyridon; Taylor, Michelle L.
Abstract: Human populations near ecosystems are used as both a proxy for dependency on ecosystems, and conversely to estimate threats. Consequently, the number of people living near coral reefs is often used in regional coral reef management, evaluation of risk at regional and global scales, and even considerations of funding needs. Human populations and their statistics, are ever‐changing and data relating to coral reefs have not been updated regularly. Here, we present an up‐to‐date analysis of the abundance, and density of people living within 5–100 km of coral reef ecosystems along with population proportion, using freely available data sets and replicable methods. We present trends of changes in human populations living near coral reefs over a 20‐year time period (2000–2020), divided by region and country, along with socio‐economic denominations such as country income category and Small Island Developing States (SIDS). We find that across 117 coral reef countries there are currently close to a billion people living within 100 km of a coral reef (~13% of the global population) compared with 762 million people in 2000. Population growth by coral reefs is higher than global averages. The Indian Ocean saw a 33% increase in populations within 100 km of a coral reef and 71% at 5 km. There are 60 countries with 100% of their population within 100 km of coral reefs. In SIDS, the proportion of the total population within 100 km of a coral reef is extremely high: 94% in 2020. Population density 5–10 km from coral reefs is 4× the global average. From 5 to 100 km, more people from lower‐middle‐income countries live by coral reefs than any other income category. Our findings provide the most up‐to‐date and extensive statistics on the regional and nation‐level differences in population trends that play a large role in coral reef health and survival. Abstract : Human populations near ecosystems are used as both a proxy for dependency on ecosystems, and conversely to estimate threats. We present trends of changes in human populations living near coral reefs over a 20‐year time period (2000‐2020). We find that across 117 coral reef countries there are currently close to a billion people living within 100 km of a coral reef (~13% of the global population) compared to 762 million people in 2000.